Spatial metaphors and the design of everyday things - Pitt, Benjamin; Casasanto, Daniel (Frontiers in Psychology, 2022)
People use space (e.g., left–right, up-down) to think about a variety of non-spatial concepts like time, number, similarity, and emotional valence. These spatial metaphors can be used to inform the design of user interfaces, which visualize many of these concepts in space. Traditionally, researchers have relied on patterns in language to discover habits of metaphorical thinking. However, advances in cognitive science have revealed that many spatial metaphors remain unspoken, shaping people’s preferences, memories, and actions independent of language – and even in contradiction to language. Here we argue that cognitive science can impact our everyday lives by informing the design of physical and digital objects via the spatial metaphors in people’s minds. We propose a simple principle for predicting which spatial metaphors organize people’s non-spatial concepts based on the structure of their linguistic, cultural, and bodily experiences. By leveraging the latent metaphorical structure of people’s minds, we can design objects and interfaces that help people think.